2018
DOI: 10.1080/03639045.2018.1503296
|View full text |Cite
|
Sign up to set email alerts
|

A quality-by-design study to develop Nifedipine nanosuspension: examining the relative impact of formulation variables, wet media milling process parameters and excipient variability on drug product quality attributes

Abstract: Wet milling is a multifunctional and the most common method to prepare a drug nanosuspension for improving the bioavailability of poorly water soluble drugs. A suitable way of preparing a high drug-loaded nifedipine nanosuspension using wet stirred media milling was investigated in the present study. Nifedipine, a poorly water soluble drug, was selected as a model drug to enhance its dissolution rate and oral bioavailability by preparing an appropriate crystalline nanosuspension. Process parameters, such as mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In the case of the binary mixture (IB/βCD), the frequency shift of the carbonyl group of IB (Table 4) [29], could be attributed to the breaking of certain intermolecular bonds (hydrogen bonds) associated with IB dimmers, largely described in the literature [33]. The shift of the CO (primary alcohol) band and the OH (associated) band of βCD compared to physical mixtures, as well as the disappearance of the NMR proton of the carboxylic group of IB and the hydroxyls peaks of βCD (2,3,6) suggested the presence of hydrogen bonds between the carboxylic group of IB and hydroxyl groups of βCD [29]. DSC results ( Table 5) have shown that the ternary mixture (IB/βCD/PVP) exhibited higher glass transition temperature (Tg˃250°C).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In the case of the binary mixture (IB/βCD), the frequency shift of the carbonyl group of IB (Table 4) [29], could be attributed to the breaking of certain intermolecular bonds (hydrogen bonds) associated with IB dimmers, largely described in the literature [33]. The shift of the CO (primary alcohol) band and the OH (associated) band of βCD compared to physical mixtures, as well as the disappearance of the NMR proton of the carboxylic group of IB and the hydroxyls peaks of βCD (2,3,6) suggested the presence of hydrogen bonds between the carboxylic group of IB and hydroxyl groups of βCD [29]. DSC results ( Table 5) have shown that the ternary mixture (IB/βCD/PVP) exhibited higher glass transition temperature (Tg˃250°C).…”
Section: Resultsmentioning
confidence: 87%
“…The presence of these two carriers has increased the glass transition temperature of Indomethacin, the Tg of ternary system was higher than that of binary ground mixtures (IM-SiO 2 , Table 1. Some examples of drug molecules exhibiting solubility enhancement by binary solid dispersion using co-milling technique [1][2][3][4][5][6][7][8][9]. IM-Mg(OH) 2 ).…”
Section: Ternary Solid Dispersion: a New Alternative To Promote Drug mentioning
confidence: 99%
See 1 more Smart Citation
“…Both nanosuspensions prepared with stabilizer showed a surface charge of approximately − 20 mV, whereas a neutral charge was observed in ISL-MS. The negative surface charge of the nanosuspensions prepared with HPC SSL and PVP K30 as stabilizers has been reported in many studies [24][25]. The morphology of all samples were assessed by SEM and TEM, presented in ▶ Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The advent of nanotechnology, which can produce nanoscale particles with novel functional properties, offers a potential solution to the aforementioned drawbacks. Nanotechnology has, for example, been used to enhance the bioavailability of certain antibiotics [14] and has also been applied to produce different targeted drugs for the treatment of different diseases [1517], and various nanosuspensions have been successfully applied [18, 19]. Nanoparticles can also be prepared using a variety of different processes, including reverse solvent, homogenization pressure, milling, and the production of self-nanoemulsifying self-nanosuspensions [20].…”
Section: Introductionmentioning
confidence: 99%